2018
DOI: 10.1063/1.5026715
|View full text |Cite
|
Sign up to set email alerts
|

Effect of film thickness on the ferroelectric and dielectric properties of low-temperature (400 °C) Hf0.5Zr0.5O2 films

Abstract: We report on the effect of the Hf0.5Zr0.5O2 (HZO) film thickness on the ferroelectric and dielectric properties using pulse write/read measurements. HZO films of thicknesses ranging from 5 to 20 nm were annealed at 400 °C for 1 min in a nitrogen ambient to be compatible with the back-end of the line thermal budget. As the HZO film thickness decreases, low-voltage operation (1.0 V or less) can be achieved without the dead layer effect, although switching polarization (Psw) tends to decrease due to the smaller g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
110
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 16 publications
3
110
0
Order By: Relevance
“…In addition, the thickness of each layer, including the HZO film (10 nm) and the TiN top and bottom electrodes (90 nm), was confirmed by cross-sectional transmission electron microscopy (see Figure 1 ). These thickness values were chosen deliberately so as to obtain excellent ferroelectric properties as reported in previous studies [ 2 , 16 ]. Based on this conventional process, the effect of TiN top and bottom electrodes on ferroelectric HZO films was investigated by changing the order of the RTA process and/or performing an additional furnace annealing in hydrogen-containing ambience for 30 min at 400 °C (i.e., FGA).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the thickness of each layer, including the HZO film (10 nm) and the TiN top and bottom electrodes (90 nm), was confirmed by cross-sectional transmission electron microscopy (see Figure 1 ). These thickness values were chosen deliberately so as to obtain excellent ferroelectric properties as reported in previous studies [ 2 , 16 ]. Based on this conventional process, the effect of TiN top and bottom electrodes on ferroelectric HZO films was investigated by changing the order of the RTA process and/or performing an additional furnace annealing in hydrogen-containing ambience for 30 min at 400 °C (i.e., FGA).…”
Section: Methodsmentioning
confidence: 99%
“…This ratio can be easily realized using common deposition techniques like atomic layer deposition (ALD) with a homogenous concentration throughout the film. 2) The FE properties of HZO films can be achieved at low process temperatures of about 400 °C . This is most likely due to the low crystallization temperature of ZrO 2 compared with other potential high‐k oxides .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that thin HZO films could be crystallized successfully in the desired FE phase by applying rapid thermal annealing (RTA) at 400 °C and even 300 °C for 30 or 60 s. Furthermore, phase transition kinetics were studied (at prior RTA crystallized films) during supplementary annealing at different temperatures and durations to simulate the thermal profile present during the formation of the interconnects, where high‐temperature processes (up to 400 °C) occur several times and last from some minutes to hours.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the tetrakis[dimethylamino]hafnium (TDMAH) and tetrakis[dimethylamino]zirconium (TDMAZ) precursors, which have also been used to deposit the FE HZO films [21][22][23][24], have only methyl groups in their ligands. Therefore, such an adverse effect might not be serious, although the complete suppression of the thermal decomposition cannot be guaranteed.…”
Section: Introductionmentioning
confidence: 99%